Volatile Compounds Profiling of Fresh R. alba L. Blossom by Headspace—Solid Phase Microextraction and Gas Chromatography - Daniela Antonova-Nedeltcheva; Ana Dobreva; Kamelia Gechovska; Liudmil Antonov (Molecules)
The white oil-bearing rose (R. alba L.) is the second of the industrially important rose species for Bulgarian rose cultivation and essential oil production. In recent years, the interest in white oil-bearing rose has increased, following the worldwide trend for searching for new aromatic alternatives. Therefore, the purpose of the current research is to evaluate the volatile compounds profile of fresh R. alba L. flowers using headspace solid-phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC/MS). More than 75 individual compounds were identified and quantified using HS-SPME-GC/MS. The study revealed that the aroma-bearing fraction of rose volatiles consists mainly of monoterpene alcohols; 2-phenylethanol was the most abundant component (8.4–33.9%), followed by geraniol (12.8–32.5%) and citronellol + nerol (17.7–26.5%). Linalool, α-pinene, β-myrcene, and rose oxides were also observed in low concentrations. The stearopten fraction in the HS phase was observed in low concentration, with main representatives nonadecane + nonadecene, heptadecane, heneicosane, and tricosane. The HS-GC profile of the R. alba fresh flowers shows distinct differences in relative abundance of the components between the two studied clones of the population, as well as between volatiles in petals and in the whole blossom. The absence of some undesirable components, such as allergenic and potentially carcinogenic methyl eugenol in fresh R. alba blossom, makes white oil-bearing rose a promising alternative to R. damascena in perfumery, natural cosmetics, and aromatherapy.